Effect of a multifaceted educational intervention for anti-infectious measures on sepsis mortality: a cluster randomized trial - Bloos, Frank; Rüddel, Hendrik; Thomas-Rüddel, Daniel; Schwarzkopf, Daniel; Pausch, Christine; Harbarth, Stephan; Schreiber, Torsten; Gründling, Matthias; Marshall, John; Simon, Philipp; Levy, Mitchell M.; Weiss, Manfred; et al. (Intensive care medicine, 2017)
PURPOSE Guidelines recommend administering antibiotics within 1 h of sepsis recognition but this recommendation remains untested by randomized trials. This trial was set up to investigate whether survival is improved by reducing the time before initiation of antimicrobial therapy by means of a multifaceted intervention in compliance with guideline recommendations. METHODS The MEDUSA study, a prospective multicenter cluster-randomized trial, was conducted from July 2011 to July 2013 in 40 German hospitals. Hospitals were randomly allocated to receive conventional continuous medical education (CME) measures (control group) or multifaceted interventions including local quality improvement teams, educational outreach, audit, feedback, and reminders. We included 4183 patients with severe sepsis or septic shock in an intention-to-treat analysis comparing the multifaceted intervention (n = 2596) with conventional CME (n = 1587). The primary outcome was 28-day mortality. RESULTS The 28-day mortality was 35.1% (883 of 2596 patients) in the intervention group and 26.7% (403 of 1587 patients; p = 0.01) in the control group. The intervention was not a risk factor for mortality, since this difference was present from the beginning of the study and remained unaffected by the intervention. Median time to antimicrobial therapy was 1.5 h (interquartile range 0.1-4.9 h) in the intervention group and 2.0 h (0.4-5.9 h; p = 0.41) in the control group. The risk of death increased by 2% per hour delay of antimicrobial therapy and 1% per hour delay of source control, independent of group assignment. CONCLUSIONS Delay in antimicrobial therapy and source control was associated with increased mortality but the multifaceted approach was unable to change time to antimicrobial therapy in this setting and did not affect survival.